Dermoscopic 'Chaos and Clues' in the diagnosis of melanoma in situ. (2nd November 2017) - Ramji, Rajan; Valdes‐Gonzalez, Guillermo; Oakley, Amanda; Rademaker, Marius
Abstract: Background/Objective: To describe the dermoscopic features of melanoma in situ using the Chaos and Clues method. Method: Histologically proven primary melanoma in situ (MIS) diagnosed through a specialist teledermoscopy clinic were reviewed by three dermatologists. By consensus they agreed on the global dermoscopic pattern, colours, presence of chaos (asymmetry of colour and structure and more than one pattern), and each of the nine clues described for malignancy. Results: One hundred MIS in 92 patients of European ethnicity (45 males) were assessed. Mean age was 67.3 years (range 20– 95). The mean dimensions of the lesions were 11.1 × 12.0 mm (range 2.5– 31.3 × 2.3– 32.3 mm). Using pattern analysis, 82% of the lesions had three or more patterns (multicomponent) and the rest had 2 patterns. Colours included light brown (100%), dark brown (98%) and grey (75%). All MIS demonstrated chaos. The most prevalent clues were thick lines (88%), eccentric structureless areas (88%), and grey or blue structures (75%). Conclusion: Dermoscopy can be very helpful in the early diagnosis of melanoma and MIS. The Chaos and Clues method is simple to use. Its unambiguous descriptors can be successfully used to describe MIS. The presence of chaos and clues to malignancy (including thick lines, eccentric structureless areas, and blue/grey structures) should raise a red flag and lead to referral or excision.